Pengaruh Komposisi Debu Vulkanik Sinabung dan Pupuk Kandang Sapi terhadap Media Tanam pada pertumbuhan dan Produksi Tembakau Deli I (Nicotiana tabacumL.) - Edison Sada Perarih Sipayung; Jonis Ginting; Lisa Mawarni (Universitas Sumatera Utara, 2015)
The purpose of the study was to determine the effect of the composition of Sinabung volcanic ashand cow manure in the planting medium on the growth and production of Deli tobacco. Theresearch was conducted at Balai Penelitian Tembakau Deli (BPTD) Sampali, Percut Sei TuanDistrict Deli Serdang Regency North Sumatera with the height of + 15 metres above sea level,began from June until July 2014. The research was arranged with a non-factorial randomized blockdesign which is consisting of 6 treatmentsratio of top soil : volcanic ash : cow manure that is 15kg:0kg: 0kg (P0), 12kg: 2.5kg: 0.5 kg (P1), 12kg: 2kg: 1 kg (P2), 12kg: 1.5kg: 1.5 kg (P3), 12kg: 1 kg:2 kg (P4), 12kg: 0.5kg: 2.5 kg (P5). The result showed that the composition of volcanic ash and cowmanurein the planting medium significantly affected the plant height, number of leaf, stemdiameter, sand leaf length (Z), first feet leaf length (VA), sand leaf width (Z), first feet leaf width(VA), sand leaf area (Z) and first feet leaf area (VA) at 18 days after transplanting up to 50 daysafter transplanting. The composition of Sinabung volcanic ash and cow manure in the plantingmedium unsignificantly affected the sand leaf thickness (Z) and first feet leaf thickness (VA).Keywords: volcanic ash, cow manure, Deli tobacco.